Analisis Yuridis Penegakan Hukum Dan Pemenuhan Hak Dalam Konteks Universalime Dan Relativisme Hak Asasi Manusia Di Indonesia - Maya Intan Pratiwi; Syahrial Syahrial; Yonar Harada Taquas Elta (EL-EMIR Institute, 2026)
This research aims to analyze the development of human rights enforcement in Indonesia, assess the effectiveness of legal and political commitments in fulfilling human rights, and understand the influence of the concepts of universalism and relativism on human rights enforcement practices in Indonesia. This research uses a normative legal research method with a legislative and conceptual approach. Data were obtained through a literature review of laws and regulations, scientific literature, journals, and human rights-related documents. The collected data were analyzed qualitatively to gain a comprehensive understanding of the issues studied. Based on the research results, it can be concluded that human rights enforcement in Indonesia still faces various challenges. Since independence, human rights have been a complex issue involving the relationship between the state and society. Various legal and political compromises have not fully improved human rights protection effectively. Legal and political commitments also do not guarantee optimal human rights enforcement and often create new problems. Media freedom plays a crucial role in monitoring human rights violations and encouraging law enforcement. Furthermore, the application of human rights in Indonesia is influenced by the concept of relativism, which considers cultural, religious, and social aspects, resulting in differences in implementation. Therefore, international human rights standards need to be more clearly emphasized in national practice.